Evaluation of Thermodynamic Parameters of 2, 4-Dichlorophenoxyacetic Acid (2, 4-D) Adsorption - A. S. Ghatbandhe; H. G. Jahagirdar; M. K. N. Yenkie; S. D. Deosarkar (Journal of Chemistry)
Thermodynamic parameters of 2, 4-Dichlorophenoxyacetic acid (2, 4-D) adsorption were evaluated by studying the adsorption equilibrium and kinetics of 2, 4-D at different temperatures. Uptake capacity of activated carbon increases with temperature. Langmuir isotherm models were applied to experimental data of 2, 4-D adsorption. Equilibrium data fitted very well to the Langmuir equilibrium model. Adsorbent monolayer capacity , Langmuir constant and adsorption rate constant were evaluated at different temperatures for activated carbon adsorption. The activation energy of adsorption () was determined using the Arrhenius equation. Using the thermodynamic equilibrium coefficients obtained at different temperatures, the thermodynamic constants of adsorption (, , and ) were evaluated. The obtained values of thermodynamic parameters show that the adsorption of 2, 4-D is an endothermic process.